PRECISO DOS CÁLCULOS URGENTE VALE PONTO
A) 2x+5-5x+-1
B)5+6x=5x+2
C)x+2x-1-3=x
D)-3x+10-2x+8+1
E)5x-5+X=9+x
F)7x-4-x=-2x+8-3x
G)7x-4-x=-2x+8-3x
H)-x-5+4x=-7x+6x+15
I)2-4X=32-18X+12
J)2X-1=-3+X+4
K)2x+3x+9=48-8x
L)3x-2-2x-3=0
M)10-9x+2x=2-3x
N)4X-4-5x+-6+90
O)2-3x=-2x+12-3x
P)7(x-5)=3(x+1)
Q)3(x-2)=4(-x+3)
R)2(x+1)-(x-1)=0
S)5(x+1)-3(x+2)=0
T)13+4(2x-1)=5(x+2)
U)4(x+5)+3(x+5)=21
V)2(x+5)-3(5-x)=10
W)8(x-1)=8-4(2x-3)
X)5(x-3)-4(x+2)=2+3(1-2x)
Soluções para a tarefa
Respondido por
9
PRECISO DOS CÁLCULOS URGENTE VALE PONTO
A)
2x+5-5x+-1
2x - 5x + 5 - 1
- 3x + 4
-3x = -4
x = - 4/-3
x = + 4/3
B)
5+6x=5x+2
6x - 5x = 2 - 5
1x = - 3
x = -3/1
x = - 3
C)
x+2x-1-3=x
+ 3x - 4 = x
3x - x = + 4
2x = 4
x = 4/2
x = 2
D)
-3x+10-2x+8+1
- 3x - 2x + 10 + 8 + 1
- 5x + 19
- 5x = - 19
x = - 19/-5
x = + 19/5
E)
5x-5+X=9+x
5x + x - 5 = 9 + x
6x - 5 = 9 + x
6x - x = 9 + 5
5x = 14
x = 14/5
F)
7x-4-x=-2x+8-3x
7x - x - 4 = -2x - 3x + 8
6x - 4 = - 5x + 8
6x + 5x = 8 + 4
11x = 12
x = 12/11
G)
7x-4-x=-2x+8-3x
7x - x - 4 = - 2x - 3x + 8
6x - 4 = - 5x + 8
6x + 5x = 8 + 4
11x = 12
x = 12/11
H)
-x-5+4x=-7x+6x+15
-x + 4x - 5 = - 7x + 6x + 15
+ 3x - 5 = - 1x + 15
3x + 1x = 15 + 5
4x = 20
x = 20/4
x = 5
I)
2-4X=32-18X+12
2 - 4x = 32 + 12 - 18x
2 - 4x = 44 - 18x
- 4x + 18x = 44 - 2
14x = 42
x = 42/14
x = 3
J)
2X-1=-3+X+4
2x - 1 = - 3 + 4 + x
2x - 1 = 1 + x
2x - x = 1 + 1
1x = 2
x = 2/1
x = 2
K)
2x+3x+9=48-8x
5x + 9 = 48 - 8x
5x + 8x = 48 - 9
13x = 39
x = 39/13
x = 3
L)
3x-2-2x-3=0
3x - 2x - 2 - 3 = 0
1x - 5 = 0
1x = + 5
x = 5/1
x = 5
M)
10-9x+2x=2-3x
10 - 7x = 2 - 3x
- 7x + 3x = 2 - 10
- 4x = - 8
x = - 8/-4
x = + 8/4
x = 2
N)
4X-4-5x+-6+90??????????? (+)
4x - 5x - 4 + 6 + 90
- 1x - 4 + 96
- 1x + 92
- 1x = - 92
x = - 92/-1
x = + 92/1
x = 92
ou
4X-4-5x+-6+90??????????? (-)
4x - 5x - 4 - 6 + 90
- 1x - 10 + 90
-1x + 80
- 1x = - 80
x = - 80/-1
x = + 80/1
x = 80
O
2-3x=-2x+12-3x
2 - 3x = - 2x - 3x + 12
2 - 3x = - 5x + 12
- 3x + 5x = 12 - 2
3x = 10
x = 10/3
P)
7(x-5)=3(x+1)
7x - 35 = 3x + 3
7x - 3x = 3 + 35
4x = 38
x = 38/4 ( divide AMBOS por 2)
x = 19/2
Q)
3(x-2)=4(-x+3)
3x - 6 = - 4x + 12
3x + 4x + 12 + 6
7x = 18
x = 18/7
R)2(x+1)-(x-1)=0
2x + 2 - x + 1 = 0
2x - x + 2 + 1 = 0
1x + 3 = 0
1x = - 3
x = - 3/1
x = - 3
S)5(x+1)-3(x+2)=0
5x + 5 - 3x - 6 = 0
5x - 3x + 5 - 6 = 0
2x - 1 = 0
2x = + 1
x = 1/2
T)13+4(2x-1)=5(x+2)
13 + 8x - 4 = 5x + 10
13 - 4 + 8x = 5x + 10
9 + 8x = 5x + 10
8x - 5x = 10 - 9
3x = 1
x = 1/3
U)4(x+5)+3(x+5)=21
4x + 20 + 3x + 15 = 21
4x + 3x + 20 +15 = 21
7x + 35 = 21
7x = 21 - 35
7x = - 14
x = - 14/7
x = - 2
V)2(x+5)-3(5-x)=10
2x + 10 - 15 + 3x = 10
2x + 3x + 10 - 15 = 10
5x - 5 = 10
5x = 10 + 5
5x = 15
x = 15/5
x = 3
W)8(x-1)=8-4(2x-3)
8x - 8 = 8 - 8x + 12
8x - 8 = 8 + 12 - 8x
8x - 8 = 20 - 8x
8x + 8x = 20 + 8
16x = 28
x = 28/16 ( divide AMBOS por 4)
x = 7/4
X)5(x-3)-4(x+2)=2+3(1-2x)
5x - 15 - 4x - 8 = 2 + 3 - 6x
5x - 4x - 15 - 8 = 5 - 6x
1x - 23 = 5 - 6x
1x + 6x = 5 + 23
7x = 28
x = 28/7
x = 4
A)
2x+5-5x+-1
2x - 5x + 5 - 1
- 3x + 4
-3x = -4
x = - 4/-3
x = + 4/3
B)
5+6x=5x+2
6x - 5x = 2 - 5
1x = - 3
x = -3/1
x = - 3
C)
x+2x-1-3=x
+ 3x - 4 = x
3x - x = + 4
2x = 4
x = 4/2
x = 2
D)
-3x+10-2x+8+1
- 3x - 2x + 10 + 8 + 1
- 5x + 19
- 5x = - 19
x = - 19/-5
x = + 19/5
E)
5x-5+X=9+x
5x + x - 5 = 9 + x
6x - 5 = 9 + x
6x - x = 9 + 5
5x = 14
x = 14/5
F)
7x-4-x=-2x+8-3x
7x - x - 4 = -2x - 3x + 8
6x - 4 = - 5x + 8
6x + 5x = 8 + 4
11x = 12
x = 12/11
G)
7x-4-x=-2x+8-3x
7x - x - 4 = - 2x - 3x + 8
6x - 4 = - 5x + 8
6x + 5x = 8 + 4
11x = 12
x = 12/11
H)
-x-5+4x=-7x+6x+15
-x + 4x - 5 = - 7x + 6x + 15
+ 3x - 5 = - 1x + 15
3x + 1x = 15 + 5
4x = 20
x = 20/4
x = 5
I)
2-4X=32-18X+12
2 - 4x = 32 + 12 - 18x
2 - 4x = 44 - 18x
- 4x + 18x = 44 - 2
14x = 42
x = 42/14
x = 3
J)
2X-1=-3+X+4
2x - 1 = - 3 + 4 + x
2x - 1 = 1 + x
2x - x = 1 + 1
1x = 2
x = 2/1
x = 2
K)
2x+3x+9=48-8x
5x + 9 = 48 - 8x
5x + 8x = 48 - 9
13x = 39
x = 39/13
x = 3
L)
3x-2-2x-3=0
3x - 2x - 2 - 3 = 0
1x - 5 = 0
1x = + 5
x = 5/1
x = 5
M)
10-9x+2x=2-3x
10 - 7x = 2 - 3x
- 7x + 3x = 2 - 10
- 4x = - 8
x = - 8/-4
x = + 8/4
x = 2
N)
4X-4-5x+-6+90??????????? (+)
4x - 5x - 4 + 6 + 90
- 1x - 4 + 96
- 1x + 92
- 1x = - 92
x = - 92/-1
x = + 92/1
x = 92
ou
4X-4-5x+-6+90??????????? (-)
4x - 5x - 4 - 6 + 90
- 1x - 10 + 90
-1x + 80
- 1x = - 80
x = - 80/-1
x = + 80/1
x = 80
O
2-3x=-2x+12-3x
2 - 3x = - 2x - 3x + 12
2 - 3x = - 5x + 12
- 3x + 5x = 12 - 2
3x = 10
x = 10/3
P)
7(x-5)=3(x+1)
7x - 35 = 3x + 3
7x - 3x = 3 + 35
4x = 38
x = 38/4 ( divide AMBOS por 2)
x = 19/2
Q)
3(x-2)=4(-x+3)
3x - 6 = - 4x + 12
3x + 4x + 12 + 6
7x = 18
x = 18/7
R)2(x+1)-(x-1)=0
2x + 2 - x + 1 = 0
2x - x + 2 + 1 = 0
1x + 3 = 0
1x = - 3
x = - 3/1
x = - 3
S)5(x+1)-3(x+2)=0
5x + 5 - 3x - 6 = 0
5x - 3x + 5 - 6 = 0
2x - 1 = 0
2x = + 1
x = 1/2
T)13+4(2x-1)=5(x+2)
13 + 8x - 4 = 5x + 10
13 - 4 + 8x = 5x + 10
9 + 8x = 5x + 10
8x - 5x = 10 - 9
3x = 1
x = 1/3
U)4(x+5)+3(x+5)=21
4x + 20 + 3x + 15 = 21
4x + 3x + 20 +15 = 21
7x + 35 = 21
7x = 21 - 35
7x = - 14
x = - 14/7
x = - 2
V)2(x+5)-3(5-x)=10
2x + 10 - 15 + 3x = 10
2x + 3x + 10 - 15 = 10
5x - 5 = 10
5x = 10 + 5
5x = 15
x = 15/5
x = 3
W)8(x-1)=8-4(2x-3)
8x - 8 = 8 - 8x + 12
8x - 8 = 8 + 12 - 8x
8x - 8 = 20 - 8x
8x + 8x = 20 + 8
16x = 28
x = 28/16 ( divide AMBOS por 4)
x = 7/4
X)5(x-3)-4(x+2)=2+3(1-2x)
5x - 15 - 4x - 8 = 2 + 3 - 6x
5x - 4x - 15 - 8 = 5 - 6x
1x - 23 = 5 - 6x
1x + 6x = 5 + 23
7x = 28
x = 28/7
x = 4
Respondido por
5
A) 2 x + 5 - 5x = 1
2 x - 5x = 1 -5
2x - 5x = - 4
- 3x = - 4
------ --------
3 3
x = 4
_ ---------
3
2 x - 5x = 1 -5
2x - 5x = - 4
- 3x = - 4
------ --------
3 3
x = 4
_ ---------
3
julietafofa:
O final saiu errado
Perguntas interessantes